Pengaruh Beban Kerja, Lingkungan Kerja, dan Dukungan Sosial Terhadap Burnout Pustakawan Di Kota Mataram - Romadhoni, Lalu Ciptadi; Asmony, Thatok; Suryatni, Mukmin (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2015)
The objective of the research is to know and analyze the effect of workload, working environment, and social support toward burnout of librarian at Mataram City. Respondents of this research were 76 librarian of public library at Mataram City. The data was analyzed using multyple linear regression. The result of this research indicates that workload have partially positive and significant effect toward burnout of librarian, instead working environment and social support have partially negative and significant effect toward burnout of librarian. Workload, working environment, and social support have simultantly significant effect toward burnout of librarian at Mataram City. The result of this research is expected to provide input and information for management of public library at Mataram City in order to making decision to decrease burnout level of librarian.